THE EFFECT OF ISLAMIC BRANDING ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS A VARIABLE INTERVENING CASE STUDY: BSI KC CIREBON SILIWANGI - Diana Magfiroh (Green Publisher, 2022)
This study was shown to determine whether there is an influence of Islamic branding and customer satisfaction on customer loyalty at BSI KC Cirebon Siliwangi . This study uses quantitative methods with a sample size of 100 respondents. Sampling using Slovin technique with purposive sampling method . The data analysis techniques used in this study include the research instrument test, classical assumption test, hypothesis testing , path analysis and coefficient of determination test. Based on the calculation of the t test ( by partial ) Islamic branding has a positive and significant influence on customer loyalty. Islamic branding has a positive and significant effect on customer satisfaction. Customer satisfaction has a positive and significant influence on customer loyalty. Islamic branding has a positive and significant influence on customer loyalty which is mediated by customer satisfaction at BSI Cirebon Siliwangi Cirebon customers. Based on the calculation of the f test (simultaneously) customer satisfaction and Islamic branding on customer loyalty has a calculated f value greater than f table and a significance value of 0.000 <0.05. Which means, Islamic branding and customer satisfaction variables affect customer loyalty together.